Studi Komparasi Model Pembelajaran Berbasis Masalah (PBL) dengan Model Pembelajaran Projek Based Learning (PjBL) terhadap Perilaku Prososial Siswa Sekolah Dasar di Surabaya - Prastyo, Danang; Sulistyowati, Ida; Prameswari, Dinda; Viqqi, Muhammad (Universitas Mathla'ul Anwar Banten, 2023)
The purpose of this study was to find out the comparison of the application of Model the PBL with the Model PjBL on the Prosocial Behavior of Elementary School Students in Surabaya. This experimental research design uses Posttest Only Nonequivalent Posttest Design. The sample of this study was students of class V A and B at SD Margerejo Surabaya, while the population was for class V students at SDN Margerejo Surabaya. The data collection technique was carried out by giving a questionnaire with 25 questions. The results showed that there were differences in the prosocial behavior of SD Surabaya students between Model PBL and the Model PjBL.